Temporal Variations in Hematological, Immunological and Serum Biochemical Parameters of Rainbow Trout (Oncorhynchus mykiss) Acclimated to High-Saline Water in the Northern Aegean Sea - Ozalp, Bans; Ergün, Sebahatti̇n; Bulut, Musa; Yılmaz, Sevdan; Yiğit, Murat; Kesbic, Osman; Büyükateş, Yeşim (Walter de Gruyter GmbH, 2023)
Abstract The present study evaluated the health status of rainbow trout (30.24±5.34 g) acclimated to high-saline water (28‰). Among adaptation procedures, gradually-acclimated (for 48 h) fish showed best performance, which were then introduced to the offshore cage-farm for further monitoring of fish health in marine environment over a long-term period of 100 days, until harvest weight of 319.9±48.51 g. Fish health and welfare was evaluated by means of biochemical parameters (viscerasomatic index, hepatosomatic index, mesenteric fat index, and spleen somatic index), hematological parameters (serum glucose, triglyceride, cholesterol, total protein, albumin, globulin), and immune parameters (lysozyme, myeloperoxidase, respiratory burst and potential killing values). Gradual acclimation to high-saline water did not show any adverse effects on health parameters. No significant differences were found in biometric measures (P>0.05). However, a time-dependent increase was recorded in hematology markers (P<0.05) after seawater transfer, and the health status improved over long term from March 7 to June 14, 2018. All serum biochemical markers, except the total protein showed significant alterations (P<0.05) in long term but without detrimental influence by day 100. Therefore, it seems possible to expand trout farms from brackish water sites to higher saline environments up to 28‰ salinity, with no detrimental impacts on fish health, that in turn may significantly contribute to the extension of potential aquaculture sites to wider areas.
Keywords: 14. Life underwater; 6. Clean water